2017
DOI: 10.1111/cpr.12418
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA signature of steroid‐induced osteonecrosis of the femoral head

Abstract: ObjectivesSteroid‐induced osteonecrosis of the femoral head (ONFH) is a common orthopaedic disease of which early detection remains clinically challenging. Accumulating evidences indicated that circulating microRNAs (miRNAs) plays vital roles in the development of several bone diseases. However, the association between circulating miRNAs and steroid‐induced ONFH remains elusive.Materials and methodsmiRNA microarray was performed to identify the differentially abundant miRNAs in the serums of systemic lupus ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Thus, it was speculated that the dE circRNAs or miRNAs associated with blood loss could also be correlated with ONFH. Third, the dE circRNAs and miRNAs might also result from the autoimmune diseases such as SLE instead of ONFH, which has been demonstrated in previous studies (44)(45)(46). It is true that SLE itself could lead to DE miRNAs and circRNAs.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, it was speculated that the dE circRNAs or miRNAs associated with blood loss could also be correlated with ONFH. Third, the dE circRNAs and miRNAs might also result from the autoimmune diseases such as SLE instead of ONFH, which has been demonstrated in previous studies (44)(45)(46). It is true that SLE itself could lead to DE miRNAs and circRNAs.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, RT-qPCR confirmed a significant increase in the level of miR-10a-5p and a decrease in the level of miR-423-59 in the patient samples. Similarly, Li et al [16] found 11 differentially expressed miRNAs (two upregulated and nine downregulated) between the ONFH group and healthy control group. Furthermore, 42 differentially expressed miRNAs (14 upregulated and 28 downregulated) were found between the ONFH group and a control group comprising patients with systemic lupus erythematosus (SLE).…”
Section: Micrornas In Steroid-induced Onfhmentioning
confidence: 86%
“…Normal SONFH Disease Markers patients and control individuals. Their data indicated that circulating miRNAs in the serum might play notable roles in the development of SONFH and act as diagnostic biomarkers [15]. Kao et al compared miRNAs in peripheral blood by microarray and PCR, implying the possibility of using miRNAs as novel diagnostic or therapeutic targets [16].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found 229 upregulated circRNAs and 116 downregulated cir-cRNAs. We further selected eight circRNAs for preliminary qRT-PCR validation based on a combination of previous studies and the circRNA-miRNA prediction network (Table 2) [15,[26][27][28][29]. The results indicated that the RNAseq data was reliable and worthy of further study.…”
Section: Discussionmentioning
confidence: 99%